2021
DOI: 10.7150/jca.55558
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0091581 promotes glioma progression by regulating RMI1 via sponging miR-1243-5p

Abstract: Glioma is a pervasive malignancy and the main cause of cancer-related deaths worldwide. Circular RNA is an important subject of cancer research, and its role and function in glioma are poorly understood. This study demonstrated that hsa_circ_0091581 is upregulated in glioma tissues and cells. The results of the CCK-8, EdU, and transwell assays indicated that hsa_circ_0091581 promotes proliferation, migration, and invasion of glioma cells. The results of the luciferase reporter and RNA immunoprecipitation assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Two upregulated miRNAs, miR-1305, and -1243, have been less extensively investigated, with no prior evidence elucidating their roles in neurological processes or dysfunctions, but the expression of these miRNAs have been confirmed in human brain ( Hiramoto et al , 2017 ; Ludwig et al , 2016 ; Qian et al , 2021 ; Su et al , 2020 ; Zhang et al , 2017 ). These miRNAs were of particular interest, because they were highly upregulated across multiple chemicals, and shown to target mRNA molecules related to TGF-β signaling (TGF-β2, SMAD2, or SMAD4).…”
Section: Discussionmentioning
confidence: 99%
“…Two upregulated miRNAs, miR-1305, and -1243, have been less extensively investigated, with no prior evidence elucidating their roles in neurological processes or dysfunctions, but the expression of these miRNAs have been confirmed in human brain ( Hiramoto et al , 2017 ; Ludwig et al , 2016 ; Qian et al , 2021 ; Su et al , 2020 ; Zhang et al , 2017 ). These miRNAs were of particular interest, because they were highly upregulated across multiple chemicals, and shown to target mRNA molecules related to TGF-β signaling (TGF-β2, SMAD2, or SMAD4).…”
Section: Discussionmentioning
confidence: 99%
“… 121 circ‐0001801, hsa_circ_0043278, hsa_circ_0006168, circ_0001588, circMELK, circSERPINE2, circLGMN, and circ‐PITX1 were significantly up‐regulated in glioblastoma (GBM) and accelerated the glioma tumorigenesis via miR‐628‐5p/HMGB3, 122 miRNA‐638/HOXA9, 123 miR‐628‐5p/IGF1R, 124 miR‐211‐5p/YY1, and miR‐1281/ERBB4, 125 , 126 miR‐593/EphB2, 127 miR‐361‐3p/miR‐324‐5p/BCL2, 128 miR‐127‐3p/LGMN, 129 miR‐379‐5p/MAP3K2 130 axis. Multiple circRNA were identified that have potential as a therapeutic target in glioma, such as circPITX1, 131 circ_101064, 132 circ‐ATXN1, 133 circPARP4, 134 circHECTD1, 135 hsa_circ_0091581, 136 circZNF609, 137 , 138 circ_0001367, 139 , 140 circ_CLIP2, 141 circRNA‐0002109, 142 circPOSTN, 143 circCDK14, 144 and circBFAR. 145 Modulating the expression of these circRNAs may inhibit glioma development.…”
Section: Circrna and Gliomamentioning
confidence: 99%